AwAreA Regulates Morphological Development, Ochratoxin A Production, and Fungal Pathogenicity of Food Spoilage Fungus Aspergillus westerdijkiae Revealed by an Efficient Gene Targeting System - Wang, Gang; Li, Yujie; Yang, Bolei; Li, Erfeng; Wu, Wenqing; Si, Peidong; Xing, Fuguo (Frontiers in Microbiology, 2022)
Aspergillus westerdijkiae, the producer of ochratoxin A (OTA), which is of worldwide concern, is an import fungal species in agriculture, food, and industry. Here, we got the uridine auxotrophic mutant of A. westerdijkiae by deleting AwpyrG. The ΔAwpyrG could be used for bio-transformation with exogenous AfpyrG expression cassette as a selection marker. In order to enhance the efficiency of gene targeting, Awku70 and Awlig4 were homologously deleted from ΔAwpyrG. The efficiencies of homologous replacement for ΔAwku70 and ΔAwlig4 were 95.7 and 87.0% in the deletion of AwAreA, respectively, demonstrating a drastic increase from 4.3% of the wild type (WT) strain. Furthermore, the function of AwAreA was identified with AwAreA deletion mutant and the control strain ΔAwku70. AwAreA regulated the growth and conidiation of A. westerdijkiae in response to nitrogen sources. The concentration of OTA for ΔAwku70 was in the range of 19.4 to 186.9 ng/cm2 on all kinds of nitrogen sources. The OTA production influenced by the deletion of AwAreA was different based on nitrogen sources. Pathogenicity assays on pears, grapes, salted meat, and cheese showed that AwAreA acted as a negative regulator in the infection of food substrates. Therefore, the genetic methods and engineered strains enable us to substantially expand the use of A. westerdijkiae, one of more than twenty OTA-producing fungi, in the study of mycotoxin biosynthesis and regulation, and consequently to aim at providing new ways for controlling this pathogen.